Modeling of grain subdivision during severe plastic deformation by VPSC method combined with disclination analysis - Nazarov, A.A.; Enikeev, N.A.; Romanov, A.E.; Orlova, T.S.; Alexandrov, I.V.; Beyerlei, n I.J. (Физика и техника высоких давлений, 2005)
Microstructure development during severe plastic deformation by simple shear is modeled using a combination of the visco-plastic self-consistent (VPSC) method and a disclination model. Strain incompatibilities between a homogeneous effective medium and a grain are calculated by VPSC. These are assumed to result in an accumulation of disclinations in the junctions of a grain that are relaxed by a growth of low-angle dislocation boundaries from the junctions. Predicted misorientation distributions between subgrains and their parent grains agree semi-quantitatively with experimental misorientation distributions for geometrically necessary boundaries. The texture after 100% simple shear was found to be insensitive to the presence of subgrains with misorientations less than 15º.